Impact of merger and acquisition on the performance of Nepalese commercial banks - Bhandari, Sushma; Pradhan, R. S. (Nepalese Journal of Management, 2024)
This study examines the impact of merger and acquisition on the performance of Nepalese commercial banks. Gross profit margin and operating profit margin are selected as the dependent variables. The selected independent variables are return on assets, return on equity, non- performing loans, debt to equity ratio and return on operating expenses. The study is based on secondary data of 13 commercial banks with 106 observations for the period from 2010/11 to 2019/20. The data were collected from Banking and Financial Statistics, Quarterly Economic Bulletin published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of merger and acquisition on the performance of Nepalese commercial banks. The study showed that return on assets and return on equity have positive impact on gross profit margin and operating profit margin of Nepalese commercial banks after the merger. It indicates that increase in return on equity leads to increase in gross profit margin and operating profit margin. Likewise, it also implies that higher the return on assets, higher would be the gross profit margin and operating profit margin. Likewise, non-performing loans have a negative impact on gross profit margin and operating profit margin indicating that increase in the non-performing loans leads to decrease in gross profit margin and operating profit margin. Moreover, debt to equity ratio and return on operating expenses have positive impact on gross profit margin and operating profit margin. It means that increase in the debt to equity ratio leads to increase in gross profit margin and operating profit margin. In addition, increase in return on operating expenses leads to increase in gross profit margin and operating profit margin in the context of Nepalese commercial banks after the merger.